A Randomized Clinical Trial to Compare Plasmodium falciparum Gametocytemia and Infectivity After Blood-Stage or Mosquito Bite–Induced Controlled Malaria Infection. (2nd April 2020) - Alkema, Manon; Reuling, Isaie J; de Jong, Gerdie M; Lanke, Kjerstin; Coffeng, Luc E; van Gemert, Geert-Jan; van de Vegte-Bolmer, Marga; de Mast, Quirijn; van Crevel, Reinout; Ivinson, Karen; Ockenhouse, Christian F; McCarthy, James S; et al.
Abstract: Background: For malaria elimination efforts, it is important to better understand parasite transmission to mosquitoes and develop models for early-clinical evaluation of transmission-blocking interventions. Methods: In a randomized open-label trial, 24 participants were infected by bites from Plasmodium falciparum 3D7-infected mosquitoes (mosquito bite [MB]; n = 12) or by induced blood-stage malaria (IBSM) with the same parasite line (n = 12). After subcurative piperaquine treatment, asexual parasite and gametocytes kinetics were assessed, and mosquito feeding experiments were performed. Results: Study procedures were well tolerated. The median peak gametocyte density was 1304/mL (interquartile range, 308–1607/mL) after IBSM, compared with 14/mL (10–64/mL) after MB inoculation ( P < .001), despite similar peak asexual parasite densities ( P = .48). Peak gametocyte density was correlated with preceding pfap2-g transcripts, indicative of gametocyte commitment (ρ = 0.62; P = .002). Direct feeding assays resulted in mosquito infections from 9 of 12 participants after IBSM versus 0 of 12 after MB inoculation ( P < .001). Conclusions: We observed a striking effect of inoculation method on gametocyte production, suggesting higher gametocyte commitment after IBSM. Our direct comparison of MB and IBSM establishes the controlled human malaria infection transmission model, using intravenous administration of P. falciparum –infected erythrocytes as a model for early-clinical evaluation of interventions that aim to interrupt malaria transmission. Clinical Trial Registration: NCT03454048 Abstract : Plasmodium falciparum gametocyte carriage was induced in malaria-naive volunteers by mosquito bite or blood-stage inoculum. Gametocyte densities were associated with preceding gametocyte commitment transcript numbers. After blood-stage malaria, gametocyte densities were sufficiently high to allow transmission to mosquitoes.